BGP robustness testing based on RFSM - WANG Le-chun; ZHU Pei-dong; GONG Zheng-hu (Tongxin xuebao)
A systematic robustness testing approach was proposed. The testing approach first inspected the disadvantages of the original concept of FSM that mixed the function procedure and the robustness procedure. Then by adding states, events, and transitions to resist various impacts, the RFSM （robustness finite state machines）, which an FSM Model has robustness procedures, was constructed. Some important problems of generating negative test cases based on RFSM were also discussed: the characteristic sequence of robustness procedures and the test oracle. Compared with the conformance test suite, robustness testing of BGP-4 （Border Gateway Protocol 4） shows that the error handling coverage of the negative test suite generated by this approach is increased by 54 percent, and the error-detecting capability is enhanced by 2.8 times.